2022
DOI: 10.3389/fenvs.2022.953512
|View full text |Cite
|
Sign up to set email alerts
|

Tax Policies of Low Carbon in China: Effectiveness Evaluation, System Design and Prospects

Abstract: Fiscal and taxation policy tools play an important role in promoting green and low-carbon development. Based on classical tax theory, including the Potter hypothesis and the environmental Kuznets curve, this paper explores the impact of environmental tax regulation on economic growth and carbon emission reduction. We find that resource tax reform could promote green total factor productivity; however, the ad valorem reform of resource tax does not significantly raise the level of low carbon development. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Concerning financial tools, financial institutions do not provide enough credit support to low-carbon enterprises in Liaoning Province for several reasons: Firstly, the waiting period for the profitability of enterprises producing new energy-saving products is long [27], and the enterprises may end up with no profit or even a loss, which leads to the commercial banks and other institutions not daring to take the risk of approving loans for the lowcarbon enterprises; secondly, the current financial policy in Liaoning Province does not provide for tracking and supervision of low-carbon credit, which leads to the financial institutions not being able to obtain sufficient information in a timely manner to find a quick solution to the problem once the enterprise is not operating well. Thirdly, there are few financial institutions in Liaoning Province, and the financial products are too simple, which leads to the situation that the capital scale of financial institutions in Liaoning Province is not enough to cope with the strong demand for loans from the low-carbon industries.…”
Section: The Policy Toolsmentioning
confidence: 99%
“…Concerning financial tools, financial institutions do not provide enough credit support to low-carbon enterprises in Liaoning Province for several reasons: Firstly, the waiting period for the profitability of enterprises producing new energy-saving products is long [27], and the enterprises may end up with no profit or even a loss, which leads to the commercial banks and other institutions not daring to take the risk of approving loans for the lowcarbon enterprises; secondly, the current financial policy in Liaoning Province does not provide for tracking and supervision of low-carbon credit, which leads to the financial institutions not being able to obtain sufficient information in a timely manner to find a quick solution to the problem once the enterprise is not operating well. Thirdly, there are few financial institutions in Liaoning Province, and the financial products are too simple, which leads to the situation that the capital scale of financial institutions in Liaoning Province is not enough to cope with the strong demand for loans from the low-carbon industries.…”
Section: The Policy Toolsmentioning
confidence: 99%
“…Scholars in China, however, shifted from the national to the regional level due to significant regional differences. They discovered that the carbon tax effect is related to local economic development [ 25 ] and that it will cause greater economic losses in underdeveloped regions while benefiting developed regions [ 26 ]. Second, carbon emissions trading supplements the surplus and deficit, and regional cooperation and emission reduction are realized through a market-oriented approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, they proposed that under certain conditions, environmental taxes will not negatively impact enterprises (Adamou et al, 2012;Liu et al, 2022). Feng et al (2022) proved the existence of a double dividend effect in China under the low-carbon tax policy. Moreover, Atif et al (2022) suggested that technology innovation input can play a moderating role in reducing the negative environmental consequences associated with the consumption of natural resources by analyzing subsamples from developing countries (Zhu et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%